Propriedades de sistemas de pontos quânticos semicondutores acoplados e sua resposta óptica - Cabral, Luís Antônio (Universidade Federal de São Carlos, 2017)
The study of doped semiconductor quantum dots with magnetic impurities has been a challenging task when adding spin-orbit coupling and exchange interaction with asymmetry effects. The combination of all these factors within a single theoretical model, simultaneously analyzed with external fields, reveals interesting properties. Within this framework, the adjustment of the effective Zeeman splitting due to the asymmetry and the character of the ground state are determined. The effective mass model of the electronic structure, that allows combining different confinement profiles with reduction of controllable symmetry, spin-orbit interaction effects and external fields under a variety of configurations, in a systematic way has been complemented with atomistic simulations. The connection between the effective mass model and such atomistic approaches was done through a characterization of the main trends for the manganese positioning (Mn) in cells containing cadmium selenide (CdSe) quantum dots covered by zinc selenide (ZnSe), as well as the exchange interaction terms, which is calculated with a fully ab initio technique. Imperfections in nanostructures are also within the scope of this Thesis. Defects can induce magnetism in low-dimensional systems, wherein the challenge is to identify the source of this nano-magnetism in non-magnetic semiconductors, such as CdSe. In this Thesis, we present an optical evidence of this nano-magnetism due to the presence of vacancies. The formation energy analysis and the effects of the stress fields for the charged and uncharged defects under various geometries provided a better understanding of the experimental results. In addition, a study of the local deformations was performed using the molybdenum disulfide (MoS2). Within the density functional theory, an organic molecule, called azobenzene, was placed on the MoS2 layer in order to investigate the adsorption properties of the system.
Properties of coupled semiconductor quantum dot systems and their optical response
Keywords: Aproximação k·p da massa efetiva; Teoria funcional da densidade; Acoplamento spin-órbita; Efeitos de assimetria; Pontos quânticos; k·p effective mass approximation; Density functional theory; Spin-orbit coupling; Asymmetry effects; Quantum dots; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESTRUTURA ELETRONICA DE ATOMOS E MOLECULAS; TEORIA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESTUDOS DE ATOMOS E MOLECULAS ESPECIAIS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTADOS ELETRONICOS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS MAGNETICOS E PROPRIEDADES MAGNETICAS